2017
DOI: 10.1007/s11242-017-0945-6
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Chemically-Selective Monitoring of Multiphase Displacement Processes in a Carbonate Rock Using 3D Magnetic Resonance Imaging

Abstract: Accurate monitoring of multiphase displacement processes is essential for the development, validation and benchmarking of numerical models used for reservoir simulation and for asset characterization. Here we demonstrate the first application of a chemicallyselective 3D magnetic resonance imaging (MRI) technique which provides high-temporal resolution, quantitative, spatially resolved information of oil and water saturations during a dynamic imbibition core flood experiment in an Estaillades carbonate rock. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…As already mentioned for the fully sampled acquisition, a shift of 4 echoes was found to give a good balance between the SNR and the sharpness of the image. A sampling fraction of 0.25 was chosen as it gives significant reduction in the acquisition time compared to the fully sampled acquisition, which in this case is from 20 to 5 h, and still provides high‐quality images (Ramskill et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As already mentioned for the fully sampled acquisition, a shift of 4 echoes was found to give a good balance between the SNR and the sharpness of the image. A sampling fraction of 0.25 was chosen as it gives significant reduction in the acquisition time compared to the fully sampled acquisition, which in this case is from 20 to 5 h, and still provides high‐quality images (Ramskill et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…oil and water), which can potentially alter the properties of the system. Although the routinely used spatial resolution of MRI is lower (a few hundred µm), it offers a range of different noninvasive contrast mechanisms, based on, for example, fluid type via the MR chemical shift (Ramskill et al ., ), wetting properties via MR relaxation time constants (Reci et al ., ), and fluid mobility via MR measurements of molecular self‐diffusivity, flow dispersion and velocity (Mitchell et al ., ; Colbourne et al ., ; de Kort et al ., , b). Thus, the high spatial resolution MRI acquisitions enabled by the present work are of particular relevance in studying structure‐flow correlations, imaging displacement processes and mapping spatial variation in fluid‐surface interactions in rocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, CS reconstructions with a single regularisation term are considered, and the effectiveness of two different regularisation functionals, the total variation (TV) and the nuclear norm (NN), for the reconstruction of spatially-resolved propagators is explored. Total variation regularisation aids in the reconstruction of sharp edges and has already been shown to work well for MR images of heterogeneous porous media [14][15][16] and the present work explores whether it also performs well for the reconstruction of spatially-resolved propagators of flow through porous media. Nuclear norm regularisation is a relatively novel approach [21][22][23] that helps to reconstruct a domain wherein only a limited number of shapes or features exist.…”
Section: Basic Principles Of Compressed Sensingmentioning
confidence: 97%
“…To accelerate the acquisitions of multi-dimensional data such as spatially-resolved propagators, we have previously demonstrated the use of interpolation of under-sampled qspace data to reconstruct a 1D spatially-resolved displacement propagator [13], and the use of k-space under-sampling and compressed sensing (CS) to acquire velocity maps in porous media [14] and 3D images of porous media using Rapid Acquisition with Relaxation Enhancement (RARE) MRI [15,16]. Further, Paulsen et al have demonstrated the use of compressed sensing to accelerate the acquisition of a multi-dimensional diffusive propagator in an anisotropic porous medium [17].…”
Section: Displacement Propagators Are Probability Distributions Of Momentioning
confidence: 99%